Synthesis of triclinic and hexagonal SmBO3 powders by mechanically activated annealing of Sm2O3 and B2O3 blends - Akçamlı, Nazlı; Agaogullari, Duygu; Balci, Ozge; Ovecoglu, M. Lutfi; Duman, Ismail (Elsevier Sci Ltd, 2016)
Samarium borate (SmBO3) powders were fabricated from oxide raw materials by a two-step solid-state synthesis method including mechanical activation and annealing. Blends containing stoichiometric amounts of samarium oxide (Sm2O3) and boron oxide (B2O3) were mechanically activated in a high-energy ball mill and subsequently annealed in air. Afterwards, mechanically activated and annealed powders were washed with distilled water in order to remove probable unreacted B2O3 phase. The effects of mechanical activation duration (15 min, 1 h, 3 h and 9 h) and annealing temperature (700-1250 degrees C) on the resultant powders were investigated. Compositional, microstructural, physical, thermal and optical properties of the powders obtained throughout the different process steps were characterized by using an X-ray diffractometry (XRD), particle size analysis (PSA), stereomicroscopy (SM), scanning electron microscopy (SEM), transmission electron microscopy (TEM), gas pycnometry, differential scanning calorimetry (DSC), heating stage microscopy (HSM), atomic absorption spectrometry (AAS), Fourier transform infrared (FTIR) spectrometry and ultraviolet-visible spectrophotometry (UV-vis) techniques. Fine-grained and pure SmBO3 powders were successfully synthesized via a simple, feasible and scalable route, yielding both triclinic and hexagonal crystal structures. Triclinic SmBO3 powders were synthesized after mechanical activation for 1 h and annealing at 700 degrees C for 2 h. The polymorphic transformation temperature of SmBO3 powders from triclinic to hexagonal is about 1080 degrees C. Due to the effect of mechanical activation, the synthesis of triclinic SmBO3 phase and its transformation to hexagonal form were found to take place at similar to 50-100 degrees C lower temperatures than those reported in other methods. Mainly hexagonal SmBO3 powders were obtained after annealing at 1150 degrees C in the presence of a very small amount of triclinic SmBO3. The resultant powders showed intense UV absorptions in the range between 1025 and 1150 nm with minimum reflectivity of 0.57% (triclinic SmBO3 phase) and 0.68% (hexagonal SmBO3 phase) depending on their crystal structures. (C) 2016 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Powders: solid-state reaction; Samarium borate; Microstructure-final; Thermal properties; Spectroscopy